Honour - Shafak, Elif (Penguin London, 2013)
'My mother died twice. I promised myself I would not let her story be forgotten . . .' Pembe and Adem Toprak leave Turkey for London. There they make new lives for their family. Yet the traditions and beliefs of their home come with them - carried in the blood of their children, Iskender and Esma.And so begins the story of Esma a young Kurdish woman in London trying to come to terms with the terrible murder her brother has committed. Esma tells the story of her family stretching back three generations; back to her grandmother and the births of her mother and Aunt in a village on the edge of the Euphrates. Named Pembe and Jamila, meaning Pink and Beautiful rather than the names their mother wanted to call them, Destiny and Enough, the twin girls have very different futures ahead of them all of which will end in tragedy on a street in East London in 1978